Lycorine Induces Mitochondria-Dependent Apoptosis in Hepatoblastoma HepG2 Cells Through ROCK1 Activation - Liu, Wu-yi; Tang, Qin; Zhang, Qian; Hu, Chang-peng; Huang, Jing-bin; Sheng, Fang-fang; Liu, Ya-li; Zhou, Min; Lai, Wen-jing; Li, Guo-bing; Zhang, Rong (Frontiers in Pharmacology, 2019)
Lycorine, a naturally occurring compound extracted from the Amaryllidaceae plant family, has been reported to exhibit antitumour activity in various cancer cell types. In the present study, we investigated the molecular mechanisms underlying lycorine-induced apoptosis in hepatoblastoma HepG2 cells. We found that lycorine induced mitochondria-dependent apoptosis in HepG2 cells accompanied by mitochondrial permeability transition pore (mPTP) opening, mitochondrial membrane potential (MMP) loss, adenosine triphosphate (ATP) depletion, Ca2+ and cytochrome c (Cyto C) release, as well as caspase activation. Furthermore, we found Rho associated coiled-coil containing protein kinase 1 (ROCK1) cleavage/activation played a critical role in lycorine-induced mitochondrial apoptosis. In addition, the ROCK inhibitor Y-27632 was employed, and we found that co-treatment with Y-27632 partly attenuated lycorine-induced ROCK1 activation and mitochondrial apoptosis. Meanwhile, an in vivo study revealed that lycorine inhibited tumour growth and induced apoptosis in a HepG2 xenograft mouse model in association with ROCK1 activation. Taken together, all these findings suggested that lycorine induced mitochondria-dependent apoptosis through ROCK1 activation in HepG2 cells, and this may be a theoretical basis for lycorine’s anticancer effects.